Health - related Quality of Life among Nurses in Zahedan University of Medical Sciences Hospitals - Hossien Ansari; Mohammad Abbasi (بیمارستان, 2015)
Background: There is close relationship between  quality of life and human health. Since, nurses as the most important health Provider group, they  should have a desirable quality of life. This study aimed  at evaluating the quality of life and related variables among nurses in Zahedan  University of Medical Sciences hospitals.